A Liquid‐Metal‐Assisted Competitive Galvanic Reaction Strategy Toward Indium/Oxide Core−Shell Nanoparticles with Enhanced Microwave Absorption - Zhao, Biao; Yan, Zhikai; Liu, Lulu; Zhang, Yuanyuan; Guan, Li; Guo, Xiaoqin; Li, Ruosong; Che, Renchao; Zhang, Rui (Advanced functional materials, 2024)
The preparation of core–shell structured nanoparticles using the galvanic replacement reaction of liquid metals is a simple and efficient method. However, precise modulation of the core and shell components to regulate the microwave absorption performance still needs to be further explored. In this study, various types of indium/oxide core–shell nanoparticles are prepared based on a competitive galvanic reaction of gallium‐indium liquid metals. The prepared indium/oxide core–shell structured nanoparticles exhibit superior electromagnetic (EM) wave absorption properties with a minimum reflection loss (RL) of −40.25 dB at 1.7 mm and the widest effective absorption band of 6.12 GHz at 2.1 mm. The superior wave‐absorbing properties originate from the dielectric losses of the interfacial and dipole polarizations. In addition, an externally applied magnetic field improves the polarization loss and microwave dissipation to achieve a minimum RL of −45.65 dB at 2.4 mm. The liquid‐metal‐assisted competitive galvanic reaction strategies extend the variety of core–shell structured nanoparticles for electromagnetic wave absorption applications. Different kinds of indium/oxide core–shell nanoparticles are prepared via liquid‐metal‐assisted competitive galvanic reaction strategies. These nanoparticles have good wave‐absorbing properties. The microwave absorption properties arise from the intrinsic core–shell structural components, as well as lattice distortions and oxygen defects in the shell layer, which give rise to interfacial polarization and dipole polarization.